Precursory Locking Precedes Slip Events on Laboratory Fault - Will Steinhardt; Emily E. Brodsky (Geophysical Research Letters)
Abstract Earthquakes occur through repeated cycles of locking and slip. What is the relationship between transiently locked patches and the size, location, and timing of the subsequent slip events? Here we use an experimental fault made of transparent rubber to image the slip history of over 18,000 events. The soft elastic system allows for contained ruptures and thus a natural evolution of stress heterogeneity over multiple earthquake cycles. We observe a precursory locking phase preceding slip nucleation for events of all sizes. The integrated locking distance increases linearly with the moment of the eventual event. The most intense (largest slip deficit) locking events are spatially and temporally correlated with the hypocenters of the largest rupture events. These results show that the transient locking is statistically, but not deterministically, predictive of the location, timing, and size of the eventual slip event.